GOVERNMENT COMMUNICATION IN POLICY IMPLEMENTATION DIGITAL TELEVISION IN INDONESIA - Desliana Dwita; Fahmi Salsabila, Ade Hidayat (ADISAM PUBLISHER, 2025)
In order to implement policies, the government must have a communication strategy so that information about policies reaches all levels of society. This research aims to find out how government communication in the implementation of policies on digitalization of terrestrial television in Indonesia. The research was conducted using a qualitative method with the type of case study and the concept used is good governance. The results found that the government has not found the right format to communicate and coordinate with institutions and local governments in an effort to implement policies on digitalization of terrestrial television. Government communication with the concept of good governance is needed, which prioritizes transparency in the policy-making process, is responsible for the success and failure of policy implementation, and seeks to accommodate the aspirations of broadcasters and community representatives in the decision-making process and policy socialization